MANTRA DALAM NASKAH “DOA WIRID TOLAK BALA”: DESKRIPSI, ISI, DAN SUNTINGAN TEKS (Mantra in “Doa Wirid Tolak Bala Manuscript”: Codicology, Content, and Editing) - Dede Hidayatullah (Kandai, 2017)
Studies on mantra on manuscript in South Borneo are still rare. Until now, mantra studies generally focus on oral tradition. To date manuscript studies generally only emphasizes on religious texts and syair. The aim of this study is to explain codicology and content in manuscript of Doa Wirid Tolak Bala (a recitation for salvation from calamity) or DWTB. This is a philological research. The research uses a descriptive method. Based on codicology it is found out that the manuscript is written in the form of prose using Banjar language with Malay Arabic writing. Based on the content, DWTB manuscript is divided into three parts. The first section is about sunnah Hajat prayer and obedient. The second section is about buying and selling recitation. The third section is about recitation and Mantra for livelihood (pesugihan) which consist of twelve recitations, three isim, one  mantra and efficacy of basmalah.